2019
DOI: 10.1039/c9ra01031a
|View full text |Cite
|
Sign up to set email alerts
|

miR-let-7d attenuates EMT by targeting HMGA2 in silica-induced pulmonary fibrosis

Abstract: Silicosis is a serious occupational disease characterized by pulmonary chronic inflammation and progressive fibrosis. Epithelial-mesenchymal transition (EMT) of alveolar epithelial cells plays a vital role in silicosis. Recent studies discovered a variety of microRNAs (miRNAs) participating in fibrotic diseases.Here, we aimed to explore the function and mechanism of miRNA let-7d in the EMT process in silicainduced alveolar epithelial cells. To detect whether let-7d and its target HMGA2 were involved in silicai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Interestingly, the overexpression of miR-26a reduced the EMT process triggered by TGF-β in adenocarcinoma A259 cells [ 153 ]. An interesting study has evidenced that, in mice exposed to silicone to induce pulmonary fibrosis, an overexpression of miRNA let-7d led to a reduction in HMGA2 expression and inhibition of EMT; while the suppression of miRNA let-7d augmented HMGA2 expression and triggered silica-induced EMT [ 154 ].…”
Section: Epigenetics Regulation Of Emp/emt-dependent Fibrosismentioning
confidence: 99%
“…Interestingly, the overexpression of miR-26a reduced the EMT process triggered by TGF-β in adenocarcinoma A259 cells [ 153 ]. An interesting study has evidenced that, in mice exposed to silicone to induce pulmonary fibrosis, an overexpression of miRNA let-7d led to a reduction in HMGA2 expression and inhibition of EMT; while the suppression of miRNA let-7d augmented HMGA2 expression and triggered silica-induced EMT [ 154 ].…”
Section: Epigenetics Regulation Of Emp/emt-dependent Fibrosismentioning
confidence: 99%
“…Through cell and animal experiments, the researchers found that overexpression of miR-29b attenuates or even reverses the EMT process induced by silica. Yu et al [ 97 , 108 ] discovered that THP-1 macrophages that phagocytose micron-sized silica particles can reduce the expression of let-7d increase the expression of HMGA2 and then promote the EMT process of A549 cells. Zhao and Qi et al [ 81 , 82 ] detected that the expression of miR-34a-5p decreased, and the expression of SMAD4 increased in murine models of silicosis and TGF- β –stimulated A549 cells.…”
Section: Ncrnamentioning
confidence: 99%
“…And overexpression of miR-29b-2-5p or miR-34c-3p inhibited the EMT process and abrogated the profibrotic effect in vitro [ 51 ], indicating that the upregulation of miR-29b-2-5p and miR-34c-3p could play a protective role in silicosis. In addition, Yu et al found that let-7d negatively regulated silica-induced EMT and inhibited silica-induced pulmonary fibrosis, which might be partially achieved through direct binding to high mobility group protein 2 (HMGA2) [ 52 ].…”
Section: Ncrnamentioning
confidence: 99%